Risk Factors Screening for Non-Communicable Diseases Among High School Students - Hema Malini; Devia Putri Lenggogeni; Okky Adelirandy (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Currently there has been an increase in the incidence of NCDs on teenager. One of the efforts to respond to the increasing prevalence of NCDs is to develop and strengthen active early detection activities (screening). Early detection of NCDs is a way to determine the presence of NCD risk factors. Early detection is useful for finding early on the possibility that someone may have NCDs or have risk factors. Screening was conducted on 98 High School students. The screening results showed that 77 students (78.57%) did not exercise regularly, 62 students (63.27%) had the habit of sleeping late, 26 students (26.53%) had overweight, and 18 students (18.73%) had pre-hypertension. These results indicate a risk of NCDs in students. The early known risk factors for NCDs in the prevention and control can be carried out as early as possible. Therefore, screening, or early detection needs to be held in schools in collaboration with local health care facilities.